Adsorbing the 3d-transition metal atoms to effectively modulate the electronic and magnetic behaviors of zigzag SiC nanoribbons. Issue 5 (17th January 2017) - Li, Hui; Chen, Wei; Shen, Xiaopeng; Liu, Jingwei; Huang, Xuri; Yu, Guangtao
Abstract : The surface-adsorbing 3d-transition metal atoms can be used as an effective strategy to tune the electronic and magnetic behaviors of zSiCNRs. Abstract : On the basis of first-principles computations, we propose a simple and effective strategy through surface-adsorbing 3d-transition metal (TM) atoms, including Ti, Cr, Mn, Fe and Co, to modulate the electronic and magnetic behaviors of zigzag SiC nanoribbons (zSiCNRs), in view of the unique d electronic structures and intrinsic magnetic moments of TM atoms. It is revealed that like applying an electric field, the adsorption of these transition metal atoms can induce an evident change in the electrostatic potential of the substrate zSiCNRs owing to the electron transfer from the TM atom to the substrate. This can break the magnetic degeneracy of zSiCNRs and solely ferromagnetic (FM) or antiferromagnetic (AFM) metallicity and even intriguing FM or AFM half-metallicity can be observed in the TM-modified zSiCNR systems. Moreover, all these modified systems can exhibit considerably large adsorption energies ranging from −0.872 eV to −4.304 eV, indicating their considerably high structural stabilities. These intriguing findings will be advantageous for promoting excellent SiC-based nanomaterials in the practical application of spintronics and multifunctional nanodevices in the near future.